Adenine nucleotide and lysine transport in Chlamydia psittaci. - Hatch, T P (1982)
Isolated reticulate bodies of Chlamydia psittaci were found to transport ATP and ADP by an ATP-ADP exchange mechanism. ATP uptake activity was not detected in elementary bodies. The apparent Km of transport for both ATP and ADP was approximately 5 microM, and the calculated Vmax for both was about 1 nmol of nucleotide transported per min per mg of protein. ADP competitively inhibited ATP transport with a Ki of 4.5 microM. Other nucleotides tested had no effect on the uptake of ATP. A magnesium-dependent, oligomycin-sensitive ATPase (ATP phosphohydrolase, EC 3.6.1.3) was associated with reticulate bodies, and most of the transported ATP was hydrolyzed to ADP, which was exchanged for additional, extracellular nucleotide. Some ADP was hydrolyzed to AMP, which exited the cells slowly. Lysine was transported against the electrochemical gradient by reticulate bodies in the presence of ATP. Oligomycin and carbonyl cyanide p-trifluoromethoxyphenylhydrazone inhibited ATP-dependent lysine transport. Lysine exited reticulate bodies when the reticulate bodies were incubated in the presence of ADP, carbonyl cyanide p-trifluoromethoxyphenylhydrazone, or a reduced concentration of ATP. The results support the concept that chlamydiae are energy parasites which are capable of drawing upon the adenine nucleotides of their hosts, hydrolyzing ATP, and establishing an energized membrane.